Predictive and Prognostic Roles of Gut Microbial Variation in Liver Transplant - Wong, Hon Jen; Lim, Wen Hui; Ng, Cheng Han; Tan, Darren Jun Hao; Bonney, Glenn K.; Kow, Alfred W. C.; Huang, Daniel Q.; Siddiqui, Mohammad Shadab; Noureddin, Mazen; Syn, Nicholas; Muthiah, Mark D. (Frontiers in Medicine, 2022)
Patients undergoing liver transplant (LTX) typically confront a challenging postoperative journey. A dysbiotic gut microbiome is associated with the development of complications, including post-LTX allograft rejection, metabolic diseases and de novo or recurrent cancer. A major explanation of this are the bipartite interactions between the gut microbiota and host immunity, which modulates the alloimmune response towards the liver allograft. Furthermore, bacterial translocation from dysbiosis causes pathogenic changes in the concentrations of microbial metabolites like lipopolysaccharides, short-chain fatty acids (SCFAs) and Trimethylamine-N-Oxide, with links to cardiovascular disease development and diabetes mellitus. Gut dysbiosis also disrupts bile acid metabolism, with implications for various post-LTX metabolic diseases. Certain taxonomy of microbiota such as lactobacilli, F.prausnitzii and Bacteroides appear to be associated with these undesired outcomes. As such, an interesting but as yet unproven hypothesis exists as to whether induction of a “beneficial” composition of gut microbiota may improve prognosis in LTX patients. Additionally, there are roles of the microbiome as predictive and prognostic indicators for clinicians in improving patient care. Hence, the gut microbiome represents an exceptionally exciting avenue for developing novel prognostic, predictive and therapeutic applications.